Collaborative Governance National Zakat Agency (Baznas) in Improving Zakat Distribution to Mustahiq Groups in the National Level Zakat Collection Unit - Tri Alipah Mustari; Muhadam Labolo; Rossy Lambelanova (Sean Institute, 2026)
Power transformers are vital components in electric power transmission and distribution systems, transforming electrical voltage according to demand. The operational reliability of a transformer is greatly influenced by the condition of its internal insulation. One effective method for detecting abnormal conditions or early transformer failures is through Dissolved Gas Analysis (DGA), which analyzes dissolved gases in insulating oil. This study aims to analyze the results of DGA tests on a 150kV power transformer to identify the type and severity of potential internal faults. The analysis methods used include the Duval Triangle, Key Gas, and Roger's Ratio methods. The test results indicated the formation of hydrocarbon gases and other gases associated with thermal and electrical faults. Interpretation of the results using these three methods revealed that the transformer was experiencing mild to moderate thermal faults, requiring further monitoring to prevent more severe damage. This study emphasizes the importance of routine monitoring using DGA as part of a predictive maintenance program for high-voltage power transformers.